Combined supplementation with α-tocopherol and vitamin C improves the blood pressure of pediatric idiopathic nephrotic syndrome patients. (February 2019) - Mellyana, Omega; Widajat, Rochmanadji; Sekarwana, Nanan
Summary: The purpose of the present study was to investigate the effects of combined supplementation with α-tocopherol and vitamin C on blood pressures and levels of ox-LDL and NOx in with pediatric idiopathic nephrotic syndrome patients. A total of thirty-six pediatric idiopathic nephrotic syndrome patients was involved in the study, which was assigned randomly into two groups, the control group of pediatric idiopathic nephrotic syndrome patients who received a standard therapy and placebo and the group of pediatric idiopathic nephrotic syndrome patients who received a standard therapy plus α-tocopherol and vitamin C. α-tocopherol and vitamin C were administered at a dose of 10–15 mg/kg/day for 12 weeks. An analysis of lipid profile and NOx was performed by means of a spectrophotometer. An analysis of ox-LDL was performed by using the enzyme-linked immunosorbent assay technique. There was a significant decrease in the number of prehypertensive and hypertensive patients in the supplementation group relative to the control group ( p  < 0.05). There was a decrease in the value of ox-LDL and NOx in the supplementation group relative to the control group, despite no significant difference ( p  > 0.50). In conclusion, the combined supplementation with α-tocopherol and vitamin C may improve blood pressure in pediatric idiopathic nephrotic syndrome patients. Thus, combination of α-tocopherol and vitamin C can be used in the clinical management of pediatric idiopathic nephrotic syndrome.